IMPLEMENTASI PEMBELAJARAN ANDRAGOGI PERSPEKTIF KISAH-KISAH DALAM AL-QURAN DI PESANTREN NGALAH PASURUAN - Muhlis, Muhammad Muhlis (Center of Education Journal (CEJou), 2024)
The andragogy learning perspective through the stories in the Qur'an is an art of adult learning that pays attention to the needs of learners in accordance with the stories in the Qur'an, taking into account educational materials, learning orientation, self-concept, and motivation to learn, especially in Islamic boarding schools (pesantren). This research aims to discover the concept of andragogy learning from the perspective of the stories in the Qur'an and analyze its implications for the learning process of students at Ngalah Pesantren in Pasuruan. This study uses a qualitative approach with a naturalistic method and a collective case study research type, using the logic of replication research design. The researcher's role involves planning, collecting, analyzing, and reporting research results. Data sources include interviews, observations, and documentation, with orientation, exploration, and focused research stages. Data analysis techniques include condensation, display, conclusion drawing, and data verification. Data validity is checked through credibility, dependability, and confirmability. The research findings at Ngalah Pesantren reveal an orientation towards Sufi values (thariqat) with empirical, intuitive, and tazkiyyah methods. This learning orientation is relevant to problem-centered and contextual approaches. The implications of andragogy learning at Ngalah Pesantren include: a) independence: initiative, executing instructions well, consistency, participatory, and devout; b) simplicity: humility and tranquility; c) brotherhood: love and positive assumptions; d) sincerity: high dedication and contentment.